Photonic and Plasmonic Metasensors. Issue 2 (17th December 2021) - Ahmadivand, Arash; Gerislioglu, Burak
Abstract: Biosensors have been designed and developed for detecting biomarkers, biomolecules, proteins, enzymes, organisms, and various types of bacterial and viral diseases since the turn of the century. Initially marred by poor sensitivity, specificity, and selectivity, the advent of the notion of photonic biosensors has successfully addressed such drawbacks. One of the hallmarks of modern pharmaceutical industries is the miniaturization of photonic platforms via continuous scaling down of their sizes, which was accomplished by leveraging the concept of artificial media. Numerous forms of photonic and plasmonic devices have been configured for next‐generation technologies since the emergence of metamaterials. Among diverse applications, the development of cost‐effective, label‐free, selective, precise, and on‐chip immunobiosensors with rapid sample‐to‐result feature has received copious interest, recently. This focused Review brings clarity to the rapidly growing body of available and in‐development metamaterials‐enabled diagnostic instruments based on inventive and promising approaches. Through centering on the operating principles of plasmonic, photonic, and hybrid metasensors, we mechanistically characterize and describe the properties of such tools and summarize the most recent achievements in devising metasensors and bioimaging tools with high precision. This insightful understanding serves as a comprehensive source for scientists, physicians, and students to construct ultradense and high‐throughput clinical screening metadevices. Abstract : This comprehensive Review brings clarity to the rapidly evolving body of available and in‐development metamaterials‐enabled diagnostic instruments based on inventive and promising approaches that have been enabled by both photonics and plasmonics principles. Through focusing on the operating mechanisms of plasmonic, photonic, and hybrid metasensors, this systematic understanding discusses the properties of such tools in practical diagnostic assays.